Liming and Fertilization on the Growth of Eucalyptus benthamii and Eucalyptus dunnii in Brazil. (30th October 2020) - Pereira da Rosa, Diego; Navroski, Marcio Carlos; De Oliveira Pereira, Mariane; Borsoi, Geedre Adriano; Nascimento, Bruno; De Andrade, Ramon Silveira; Moraes, Carolina
Abstract : The use of mineral fertilizers has shown substantial productivity gains for the vast majority of Eucalyptus forests. The objective of the present work is to evaluate the response of Eucalyptus benthamii and Eucalyptus dunnii at 48 months of age, to different doses of limestone, soluble NPK, and natural phosphates. The experiment was conducted in a plantation located in South Brazil. The experimental design was a randomized block with three replications, and the treatments consisted of combinations of doses of natural phosphate (NP) (0, 400, 600, and 800 kg ha −1 of Gafsa reactive NP P2 O5 ), limestone (0, 3, 5, 6, and 10 Mg ha −1 of dolomitic limestone), and mineral fertilizer–NPK (0, 100, 133, and 167 kg ha −1 of mixed mineral fertilizer 6-30-6). Height and diameter measurements were taken after 48 months. There was a positive response with the increase of NPK fertilizer dose, and the dose where the highest averages were obtained was 167 kg ha −1 . The doses of NP had significant effects on the increase of the variables up to 600 kg ha −1, also the averages decreased with the increase of the dosage. For liming, positive results were observed from its absence to the maximum dose, justifying its use in minimum dose in order to supply the necessary amounts of Ca and Mg in the soil. The use of NPK, natural phosphate, and limestone is recommended, causing an increase in the growth of both species of Eucalyptus studied.